Pendidikan Kesehatan Tentang Perawatan Payudara Pada Ibu Hamil - Septiani, Tety; Dewi, Ratna; Ernawati, Wahyu (Yayasan Daarul Huda Kruengmane, 2024)
Background: Breast care must be introduced to mothers when the pregnancy enters the third trimester (gestational age >28 weeks), the midwife will prepare the mother both physically and psychologically to provide exclusive breastfeeding with breast care counseling. Breast care counseling includes breast and nipple hygiene, breast massage and bra use, all of which aim to increase breast milk production (Fajriani, 2021). Breast care takes the form of breast massage to improve blood circulation, caring for the nipples so they are clean and don't get sore easily. Breast care should be carried out as early as possible during pregnancy in an effort to prepare the shape and function of the breasts before lactation occurs. Lack of preparation for breast care can result in sucking problems in babies due to small or drooping nipples. Another consequence of this is that breast milk production is delayed and the cleanliness of the mother's breasts is not guaranteed, which can endanger the baby's health. The aim of this community service activity (PKM) is to provide education to mothers about breast care techniques. Method: This activity is carried out directly face to face with the target so that it is more effective, convincing and familiarizes the relationship between the instructor and the target as well as a faster response. Results: Mother understands the benefits of breast care and is able to demonstrate breast care techniques again. Conclusion: Explanations about breast care in the form of education and demonstrations provide many positive influences.